2020
DOI: 10.1001/jamanetworkopen.2020.15633
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Digital Cognitive Behavior Therapy–Guided Self-Help Intervention for Eating Disorders in College Women

Abstract: Key Points Question Does a coached, digital, cognitive behavior therapy (CBT) intervention result in improved outcomes among college women with eating disorders (EDs) compared with referral to usual care? Findings In this cluster randomized clinical trial that included 690 women with binge-purge EDs from 27 US universities, the digital CBT intervention was superior to referral to usual care in decreasing ED psychopathology, compensatory behaviors, depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…This further points to the urgent need to shift away from viewing EDs as a female issue and for the development of ED prevention and intervention programs that are effective with each gender. One possible solution to reduce the treatment gap is to implement online EDs preventive and treatment interventions, which have been shown to be affordable (Kass et al, 2017), effective in reducing eating‐related psychopathology among community samples across genders (Beintner, Jacobi, & Taylor, 2012; Fitzsimmons‐Craft et al, 2020; Saekow et al, 2015) and in a clinical sample (Haderlein, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This further points to the urgent need to shift away from viewing EDs as a female issue and for the development of ED prevention and intervention programs that are effective with each gender. One possible solution to reduce the treatment gap is to implement online EDs preventive and treatment interventions, which have been shown to be affordable (Kass et al, 2017), effective in reducing eating‐related psychopathology among community samples across genders (Beintner, Jacobi, & Taylor, 2012; Fitzsimmons‐Craft et al, 2020; Saekow et al, 2015) and in a clinical sample (Haderlein, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Third, only 15.5% of respondents reported initiating treatment at 2‐month follow‐up. Prior work found that 26.2% of college students screening positive for AN initiated treatment over 9 months (Fitzsimmons‐Craft et al, in press), and 28% of college students screening positive for binge‐type EDs and referred to on‐campus care sought treatment over 2 years (Fitzsimmons‐Craft et al, 2020). Current study rates were thus lower, but reported over a shorter time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Screen results were grouped into three ED groups: (a) no ED or risk for ARFID; (b) high risk for an ED; and (iii) clinical/subclinical AN, BN, BED, or UFED. The disorders in the clinical group reflect increased weight and shape concerns and an internalization of the thin ideal (Fairburn, 2008), and individuals with BN, BED, and UFED have been included in studies testing online interventions for EDs (Fitzsimmons‐Craft et al, 2019; Fitzsimmons‐Craft et al, 2020). In contrast, an ARFID diagnosis excludes body image disturbances (American Psychiatric Association, 2013).…”
Section: Methodsmentioning
confidence: 99%